What I learned from Shahabuddin Ahmed - Hasan, Md. Mahmudul (2022)
I am not very sure when Bangladesh will see another February 27, 1991 election that set a historic record of fairness under the watch of Shahabuddin Ahmed. In order to treasure the moment of democratic exhilaration that all of us experienced on that day, can’t we declare it the Day of Democracy in Bangladesh? I believe that will be a great way to pay tribute to Shahabuddin Ahmad for what he contributed to our country and to our democratic life.